2020
DOI: 10.1093/humrep/deaa137
|View full text |Cite
|
Sign up to set email alerts
|

Delay in IVF treatment up to 180 days does not affect pregnancy outcomes in women with diminished ovarian reserve

Abstract: STUDY QUESTION Will a delay in initiating IVF treatment affect pregnancy outcomes in infertile women with diminished ovarian reserve? SUMMARY ANSWER A delay in IVF treatment up to 180 days does not affect the live birth rate for women with diminished ovarian reserve when compared to women who initiate IVF treatment within 90 days of presentation. WHAT IS KNOWN ALREADY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…Our study can be reassuring for patients in the age range considered, who are cared with expectant management of at least eleven months before IVF as we did not nd evidence that waiting has a negative in uence on their live birth rate. These ndings may also reassure couples who have experienced or will experience delays in accessing IVF treatments due to the COVID-19 pandemic, according to similar results reported by other groups [25].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our study can be reassuring for patients in the age range considered, who are cared with expectant management of at least eleven months before IVF as we did not nd evidence that waiting has a negative in uence on their live birth rate. These ndings may also reassure couples who have experienced or will experience delays in accessing IVF treatments due to the COVID-19 pandemic, according to similar results reported by other groups [25].…”
Section: Discussionsupporting
confidence: 83%
“…More importantly, the clinical question is more often: can we delay treatment for a certain period of time without causing harm to the patient and perhaps have them conceive spontaneously? A recent retrospective study shows that in patients with reduced ovarian reserve a delay of no more than six months is not associated with worse IVF outcomes [25], but the chances of achieving pregnancy without IVF have not been investigated. So, our dilemma is still open.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that time is a key element in assisted reproduction, I believe in the importance of prioritising discussions on how to administer treatments during a health emergency over discussions on whether to administer treatments in these circumstances. While it has been reported that only a few months of delay may not necessarily affect the chances of success of fertility treatment ( Romanski et al., 2020 ), waiting times from initial diagnosis of sub-fertility to the start of fertility treatment can be lengthy. Additionally, it is unclear whether there will be further suspensions in the event of a sustained rise in infections.…”
Section: Suspending Fertility Treatmentsmentioning
confidence: 99%
“…The authors reported that discontinuation of fertility treatment for even one month in the USA could result in 369 fewer women having live birth, due to the increase in patients' age during the shutdown (20). On the opposite, another study preliminary reported that in women with diminished ovarian reserve (AMH <1.1 ng/ml) there was no difference in the live birth rate among women who initiated their IVF cycle within 90 days of their first visit due to COVID-19 pandemic compared to women who did procedures 91-180 days after initial consultation (21). Although the psychological impact of ART delayed was not evaluated in the study, these latter results may be reassuring to women with poor ovarian reserve, who may feel particularly anxious and depressed to begin their treatment and become frustrated when unexpected delays occur, as demonstrated by the logistic regression analysis of our data.…”
Section: Discussionmentioning
confidence: 99%